CUSTOMER CITIZENSHIP BEHAVIOR (CCB): THE ROLE OF BRAND EXPERIENCE AND BRAND COMMUNITY COMMITMENT AMONG AUTOMOBILE ONLINE BRAND COMMUNITY IN MALAYSIA - Aishah, Siti Noor; Shaari, Hasnizam (Journal of Technology Management and Business, 2017)
This paper aims to examine the relationship of brand experience and brand community commitment on customer citizenship behaviour (CCB), as well as the mediating effect of brand community commitment in the relationship between brand experience and customer citizenship behaviour. Data were collected via online questionnaire surveys. PLS 3.0 and bootstrapping methods were used for the data analyses. Results show that brand experience plays a significant role in influencing brand community commitment and CCB. Besides, community commitment also mediates the relationship between brand experience and customer citizenship behaviour (i.e. recommendation, helping other customers, and providing feedback). The findings suggest that marketing or service managers must create positive brand experience among the automobile customers, and create programs to enhance brand community commitment.Â